2014
DOI: 10.2147/dnnd.s40349
|View full text |Cite
|
Sign up to set email alerts
|

Neurogenic overactive bladder in spinal cord injury and multiple sclerosis: role of onabotulinumtoxinA

Abstract: People with neurogenic overactive bladder from either multiple sclerosis or spinal cord injury often suffer significant morbidity and decreased quality of life. Here we review the pathophysiology of neurogenic overactive bladder and the impact it can have on people with multiple sclerosis or spinal cord injury. We also address the various traditional treatment options and focus on the use of botulinum toxin A (specifically onabotulinumtoxinA) for this condition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…Spinal cord transection/injury models are commonly utilized to study DO, DESD, and other types of lower urinary tract (LUT) dysfunction after any injury to the spinal cord, just as traumatic, developmental, infectious, vascular, degenerative injuries, and so on (Ethans et al, 2014;Panicker, 2020). Typically, the SCI model could be achieved by complete transection at different levels of spinal cord in different animals, particularly cats (de Groat et al, 1990) and rats (Shaker et al, 2003;Behr-Roussel et al, 2011).…”
Section: Animal Models Of Neurogenic Overactive Bladdermentioning
confidence: 99%
See 1 more Smart Citation
“…Spinal cord transection/injury models are commonly utilized to study DO, DESD, and other types of lower urinary tract (LUT) dysfunction after any injury to the spinal cord, just as traumatic, developmental, infectious, vascular, degenerative injuries, and so on (Ethans et al, 2014;Panicker, 2020). Typically, the SCI model could be achieved by complete transection at different levels of spinal cord in different animals, particularly cats (de Groat et al, 1990) and rats (Shaker et al, 2003;Behr-Roussel et al, 2011).…”
Section: Animal Models Of Neurogenic Overactive Bladdermentioning
confidence: 99%
“…The mechanism underlying MS-related OAB symptoms is mainly due to the DO induced by suprapontine lesions, with disruption or lack of descending inhibitory impulses from the brain to the spinal cord (Ethans et al, 2014). Many studies about urodynamics in MS cases have demonstrated detrusor hyperreflexia or hyporeflexia (Akkoç et al, 2016;Wang et al, 2016).…”
Section: Neurological Conditions With Overactive Bladder Symptoms Multiple Sclerosis and Related Neuroinflammatory Disordersmentioning
confidence: 99%
“…Overactive bladder syndrome (OAB) is defined by the International Continence Society (ICS) as urinary urgency, usually with urinary frequency and nocturia, with or without urgency urinary incontinence [1,2]. Ethans et al indicated that OAB can be further differentiated into cases having neurological causes (mostly multiple sclerosis) or as being idiopathic [3].…”
Section: Introductionmentioning
confidence: 99%